1999
DOI: 10.1046/j.1439-0507.1999.00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Dosage adjustment of fluconazole during continuous renal replacement therapy (CAVH, CVVH, CAVHD, CVVHD)

Abstract: Continuous arterio-venous haemofiltration (CAVH), continuous veno-venous haemofiltration (CVVH), continuous arterio-venous haemodialysis (CAVHD) and continuous veno-venous haemodialysis (CVVHD) are increasingly used in patients with acute renal failure (ARF). The elimination rate of fluconazole varies considerably depending on the procedure used. (In Germany, fluconazole is approved for the treatment of life-threatening fungal infections caused by Candida spp. and Cryptococcus neoformans at a dosage of up to 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 8 publications
0
9
0
3
Order By: Relevance
“…Drug–drug interactions with fluconazole complicate dosing with the immunosuppressants ciclosporin, tacrolimus, and sirolimus [32]. Fluconazole requires dose adjustment in patients receiving RRT, as the procedure results in a significant clearance of fluconazole, which varies depending on the technique used [33, 34]. Although nephrotoxicity risk is reduced with liposomal amphotericin B compared with amphotericin B deoxycholate [15, 17], it may still limit its use [20, 35], especially in recipients with renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Drug–drug interactions with fluconazole complicate dosing with the immunosuppressants ciclosporin, tacrolimus, and sirolimus [32]. Fluconazole requires dose adjustment in patients receiving RRT, as the procedure results in a significant clearance of fluconazole, which varies depending on the technique used [33, 34]. Although nephrotoxicity risk is reduced with liposomal amphotericin B compared with amphotericin B deoxycholate [15, 17], it may still limit its use [20, 35], especially in recipients with renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…3D to F). Several studies have previously recommended a daily dose of 800 mg with CVVHDF (4,8,12,14,20,22,26,36,39). However, due to study design and analysis methods, these recommendations do not accurately identify between-subject variability, the effect of covariates such as filter age, or the likely probability of attainment at steady state.…”
Section: Discussionmentioning
confidence: 99%
“…It is normally extensively reabsorbed by the kidneys (9), and it has previously been validated as a marker for renal reabsorption (35). However, in patients with severely impaired kidney function, the ability for tubular reabsorption is unlikely, and it could considerably alter the clearance of fluconazole when combined with continuous RRT (8,20,26,38,39). As a consequence, this could significantly influence the fAUC 0-24 /MIC ratio of fluconazole, thereby compromising its desired therapeutic response.…”
mentioning
confidence: 99%
“…A number of pharmacokinetic characteristics predict that fluconazole will be significantly removed during RRT: these include a low molecular weight, relatively small volume of distribution, low degree of protein binding, and elimination of unmetabolized drug through predominantly renal mechanisms (Table 1). A number of studies have shown that fluconazole is readily removed during various types of RRT, including IHD, CVVH, CVVHD, and CVVHDF [14][15][16][17][18]. Indeed, the total systemic clearance of fluconazole during CVVHDF at ultrafiltration rates of 1 to 2 L per hour may exceed that of patients with normal renal function, and up to 88% to 99% of the administered fluconazole dose may be removed over a 24-hour period [14,16].…”
Section: Fluconazolementioning
confidence: 99%